Effect of Lung Protective Ventilation Combined With Flurbiprofen Axetil on Immune Function During Thoracoscopic Radical Resection of Lung Cancer - Yuan, Jia; Cen, Shenghua; Li, Jingjing; Wang, Kun; Chen, Qixu; Li, Hongbin; Zhang, Yan (Frontiers in Surgery, 2022)
Abstract The decreased immune function of patients with lung cancer has always been the focus of clinical attention. However, the stress response caused by surgery, anesthesia and pain will further reduce the body's immune function and affect the prognosis of patients to a certain extent. Studies have found that both protective ventilation and pre-treatment with flurbiprofen axetil can reduce the immunosuppression of stress response. In this study, 120 lung cancer patients treated with video-assisted thoracoscopic radical resection were divided into group A, group B, group C and group D, which were treated with conventional mechanical ventilation, lung protective ventilation, conventional mechanical ventilation+flurbiprofen axetil and lung protective ventilation+flurbiprofen axetil, respectively. The results showed that the levels of CD3+, CD4+, CD4/CD8+, and NK in groups A, B and C were lower than T0 on T1, T2 and T3, while those indicators in group D were lower than T0 on T1 and T2 (P < 0.05). The above indicators in group D were higher than those in the other three groups on T1, T2 and T3 (P < 0.05). The above indicators were statistically significant compared with those in group A and group C, group B and group D, and group A and group B at T1, T2 and T3 (P < 0.05). The comparisons of CD3+, CD4+, CD4/CD8+, and NK among the four groups within different time groups, and the repeated ‐ measures analysis of variance (repeated ‐ measures ANOVA) showed that there were interactions among time, group, and between groups × within groups (P < 0.05). It was confirmed that lung protective ventilation combined with flurbiprofen axetil could alleviate the immunosuppression of patients undergoing thoracoscopic radical lung cancer, providing a new idea for clinical treatment.